Rapid In Vitro Propagation Technique For Sugarcane Variety 018 - SATPAL SINGH BISHT; AJIT KUMAR ROUTRAY; ROJITA MISHRA (International Journal of Pharma and Bio Sciences, 2011)
Indian economy gains 1.9% of National GDP by sugarcane cultivation. Plant growth hormones such as BAP, NAA, 2, 4-D, Kn, IBA were used to initiate cultures. A successful procedure was established in the culture conditions of variety 018. MS medium supplemented with 2,4-D (3.0 mg/l) , Kn (0.2 mg/l) and 3% sucrose was the best for the initiation of callusing from leaves and MS medium supplemented with BAP (1.0 mg/l), Kn (0.5mg/l) and 3% sucrose was best for shooting in eye bud from nodal region. The best multiplication rate of shooting in case of nodal eye bud was in MS medium supplemented with BAP(0.1 mg/l), Kn (0.5) & NAA (0.25 mg/L) and 3% sucrose where as for leaves MS medium supplemented with BAP (4.0 mg/l) , IBA (0.5 mg/L) and 3% sucrose. Root system was found in ½ MS medium with NAA (3.0 mg/l) and 6% sucrose.